High frequency continuous birefringence-induced oscillations in spin-polarized vertical-cavity surface-emitting lasers - Torre, Maria Susana (2017)
Sustained, large amplitude and tunable birefringenceinduced oscillations are obtained in a spin-vertical cavity surface-emitting laser (spin-VCSEL). Experimental evidence is provided using a spin-VCSEL operating at 1300 nm, under continuous-wave optical pumping and at room temperature. Numerical and stability analyses are performed to interpret the experiments and to identify the combined effects of pump ellipticity, spin relaxation rate, and cavity birefringence. Importantly, the frequency of the induced oscillations is determined by the device's birefringence rate, which can be tuned to very large values. This opens the path for ultrafast spin-lasers operating at record frequencies exceeding those possible in traditional semiconductor lasers and with ample expected impact in disparate disciplines (e.g., datacomms, spectroscopy).